Stability-indicating liquid chromatographic and UV spectrophotometric methods for the quantification of ciprofibrate in capsules and tablets - Fernanda Macke Hellwig; Rafael Henrique Dias Reis; Suzana Del Rosso Barbosa; Marcelo Donadel Malesuik (Universidade de São Paulo, 2015)
This study describes the development and evaluation of stability-indicating liquid chromatographic (LC) and UV spectrophotometric methods for the quantification of ciprofibrate (CPF) in tablets and capsules. Isocratic LC separation was achieved on a RP18 column using a mobile phase of o-phosphoric acid (0.1% v/v), adjusted to pH 3.0 with triethylamine (10% v/v) and acetonitrile (35:65 v/v), with a flow rate of 1.0 mL min-1. Detection was achieved with a photodiode array detector at 233 nm. For the spectrophotometric analysis, ethanol and water were used as the solvent and a wavelength of 233 nm was selected for the detection. The methods were validated according to International Conference on Harmonization (ICH) guidelines for validating analytical procedures. Statistical analysis showed no significant difference between the results obtained by the two methods. The proposed methods were successfully applied to the CPF quality-control analysis of tablets and capsules.